Gaya Kepemimpinan Kepala Desa Ongulero Kecamatan Marawola Barat Kabupaten Sigi - Alifa Raema Widana (Sekolah Tinggi Ilmu Administrasi (STIA) Pembangunan Palu, 2023)
Leadership is a person's ability to position themselves according to time and space and be able to understand their duties and responsibilities, so that satisfactory results are obtained to achieve good employee performance. Therefore, a village head must know and be able to play his role as a leader in his village. The aim of this research is to find out the leadership style of the Head of Ongulero Village, West Marawola District, Sigi Regency. The informants in this research were Ongulero Village office officials. So the informants are the Village Secretary, Head of Government, Head of Development, Community. The results of the research show that to determine the leadership style in carrying out its duties and functions in the Ongulero Village office, West Marawola District, Sigi Regency. The author chose a theory that is considered more suitable to be applied to government organizations, in this case Ongulero Village, West Marawola District, Sigi Regency, is the theory of Harbani Pasoloang (2008: 50-51), namely: Instruction, Consultation, Participation, Delegation. So it can be concluded that the author concludes that the Leadership Style of the Head of Ongulero Village, West Marawola District, Sigi Regency, as measured by the four indicators, which is considered to be working well is the Instruction indicator/dimension, while in the indicators/dimensions of Consultation, Participation and Delegation the results are not working well.